2015
DOI: 10.1007/s00125-014-3481-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of global gene expression profiles suggests a role of acute inflammation in type 3C diabetes mellitus caused by pancreatic ductal adenocarcinoma

Abstract: Aims/hypothesis Pancreatic ductal adenocarcinoma (PDAC) can cause type 3C diabetes, known as PDAC-associated diabetes mellitus (PDAC-DM), but the mechanism is unknown. This study aimed to reveal the mechanism. Methods PDAC lesions from patients with or without PDAC-DM (n=4 in each group) were individually profiled for 23,512 mRNAs with microarrays. Bioinformatic analysis and in vivo and in vitro assays were then conducted. Results We determined that 2,778 genes were differentially expressed; over-representatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…All patients who donated their tissue samples for biomedical research, which were approved by the ethics committee of Guangdong Provincial People's Hospital, have signed informed consent forms. To detect the mRNA expression of LBP, quantitative reverse transcriptase-polymerase chain reaction (PCR) was performed as described previously (25). To achieve robust single-base specificity, a novel PCR-based method, named quantitative analysis of single-base methylation (QASM), was used to detect cg08351331 status in HCC samples (26).…”
Section: Validation Of Lbp and Cg08351331 In Hcc Samplesmentioning
confidence: 99%
“…All patients who donated their tissue samples for biomedical research, which were approved by the ethics committee of Guangdong Provincial People's Hospital, have signed informed consent forms. To detect the mRNA expression of LBP, quantitative reverse transcriptase-polymerase chain reaction (PCR) was performed as described previously (25). To achieve robust single-base specificity, a novel PCR-based method, named quantitative analysis of single-base methylation (QASM), was used to detect cg08351331 status in HCC samples (26).…”
Section: Validation Of Lbp and Cg08351331 In Hcc Samplesmentioning
confidence: 99%
“…Notably, PC harbors a chronic inflammatory microenvironment (16), and chronic inflammation is a crucial mediator of insulin resistance (17). Analysis of gene ontology also showed that secretory genes differentially expressed in tumors of patients with PCDM are related mainly to inflammation (18). Therefore, we hypothesized that insulin resistance and PCDM are induced by overexpression of specific inflammatory mediators in PC, and blood levels of those mediators may facilitate differentiation between PCDM and type 2 diabetes.…”
mentioning
confidence: 97%
“…Gao et al reported that the TNFSF13 level in serum was significantly associated with the diabetic status of patients with pancreatic ductal adenocarcinoma-associated diabetes [25]. …”
Section: Discussionmentioning
confidence: 99%